An Observation on Website Features Towards Air Asia e-Ticketing Website in the Context of Online Purchasing - Ismail, Nor Alina; Rajamanickam, Leelavathi; Daud, Siti Norbaya (International Journal of Psychosocial Rehabilitation, 2020)
During the past ten years the impact of the internet on channel selection has been dramatic and pervasive throughout the business world. Yet strong arguments can be made that few industries have been as invasively affected as has the airlines industry. Currently travellers increasingly choose the websites to search for flight ticket or other things. This paper provides a report of website observation towards website features that influenced customer to purchase flight ticket online. The study focused on Air Asia e-ticketing website. Hence, the websites features was considered based on the three stages in online purchasing cycle (pre-purchase, purchase and post-purchase).